Finite Element Analysis of Strength Degradation and Interface Behavior Controlling Bund Wall Stability in an Ex-Mining Pit - Revia Oktaviani; Tommy Trides; Albertus Juvensius Pontus; Afdal Jamil Tanjung; Haviluddin Haviluddin (Malikussaleh University, Aceh, Indonesia, 2026)
This study presents a finite element analysis of the stability and interface behavior of a bund wall constructed under tropical mining conditions at the Banda Mine, East Kalimantan, Indonesia. The research aims to evaluate the effects of strength degradation and geometric interfaces on the overall stability of the embankment system, which was designed to retain overburden material and mitigate slope failure under combined rainfall and seismic loading. The bund wall, with an overall height of 75 m and a base width of 130 m, was constructed using compacted sandy loam sourced from site overburden. Laboratory testing determined the geotechnical parameters of the materials, including soft clay, sandy loam, and siltstone foundation. Finite element modeling was performed on six critical cross sections to simulate progressive strength reduction representing 0%, 25%, and 50% cohesion loss. The calculated factors of safety ranged from 1.87 to 2.55 along the slope, 3.40 to 5.81 at the bund wall base, and 7.79 to 10.27 within the foundation, confirming overall structural stability under all modeled scenarios. However, local reductions in stability were observed near the interface zones and the central section of the wall at depths exceeding 25 m. These findings highlight the influence of interface geometry and strength degradation on stability performance and emphasize the need for improved compaction and continuous stress monitoring during operation